Tuntutan Kemahiran Komunikasi Antarpribadi dalam Profesi: Perspektif Hongkong dan Indonesia - Lesmana, Tjipta (Jurnal Ilmu Komunikasi, 2006)
Abstract: Hong Kong is widely acknowledged as one of the busiest financial and economic center in the world. Hundreds of world-class companies establish their representative offices in this former British colony. For the effectiveness of their operations, the companies, using newspaper advertisement, actively recruits intelligent and smart employees. Current research was designed to investigate how companies appreciate interpersonal communication skills when hiring new employees announced in the advertisements. Content of weekend edition of South China Morning Post, called âClassified Postâ (about 100 pages), was scrutinized. To gain a little insight of the same phenomenon in Indonesia some editions of âKlasikaâ section of daily Kompas was analyzed. It was found that awareness of interpersonal communication skill, in general, was fairly high in the case of Hong Kong (38.2%), but only 9.83% for Indonesia. The top two professions in Hong Kong requiring this skill was public relations official (38.1%) and sale persons (32%). In the case of Indonesia, it was secretary and finance officials.